(untitled) (Carte Romanze, 2023)
The contributions aimed at offering resolving hypotheses on the ambiguity of some toponyms mentioned in the Cantigas de Santa María are still scarce. The present work, the result of research conducted as part of a larger project, with the aim of undertaking a systematic study of the nominal entities (toponyms and anthroponyms) that appear in the Cantigas dedicated to the Virgin, deals with the cases of Camela (CSM 165 ), Luzerna (CSM 405) and Romania (CSM 231). These have in fact received divergent readings from critics, with a consequent alteration of the space in which the corresponding literary miracles occur. The study aims to integrate the already good observations of Walter Mettmann with linguistic, historical and literary data to arrive at a more secure identification of the toponyms in question